ALGORITHMIC THINKING IN HIGHER EDUCATION: DETERMINING OBSERVABLE AND MEASURABLE CONTENT - Byrka, Marian; Sushchenko, Andrii; Luchko, Volodymyr; Perun, Galina; Luchko, Victoria (Information technologies and learning tools, 2024)
Nowadays algorithmic thinking, as a key demand and the main requirement of technology-based society, extensively expands outwards the computer science area and rapidly becomes a meaningful instrumentality for effective realization of any information activities with or without ICT. This instrumentality creates new opportunities and possibilities for improvement of the effectiveness of any educational professional activities in the higher education context by creating problem-solving algorithms completely within the ICT area, as well as non-ICT-based algorithms that provide clear technological step-by-step instructions for solving a diversity of educational problems. Although attention to algorithmic thinking as scientific phenomenon is increasing, the studies aimed at determining the algorithmic thinking content in observable and measurable statements have not been conducted yet and its great potential is still undiscovered. The purpose of this study is to identify, clarify, and categorize algorithmic thinking content in observable and measurable knowledge, skills, and abilities statements (KSAs). The study is a mixed-methods type of development research carried out in 4 stages: 1) extraction of the KSA statements from the extant scientific literature related to algorithmic thinking; 2) design of The Algorithmic Thinking Content Survey (ATCS) based on the five steps Universal Sequence of an Algorithm Development (USAD); 3) administration of the ATCS on a wide variety of educational professionals (N = 117); 4) data analysis aimed to obtain the content of algorithmic thinking in observable and measurable KSA statements. The design of the ATCS is also based on algorithmic thinking as a complex phenomenon that integrates five types of thinking: abstract, logical, figurative, conceptual, and constructive. The administration of the ATCS involved 117 experts – educational professionals (11 professors who teach courses concerning algorithms and computer science, 23 practicing teachers of informatics, 35 students in the 3rd year of Informatics teacher training program, and 48 master students of informatics). Expert validation of algorithmic thinking content in knowledge, skills, and abilities statements was obtained through the Likert scale. One hundred KSA statements of algorithmic thinking content were obtained (32 statements of knowledge, 38 statements of skills, and 30 statements of abilities). Алгоритмічне мислення як ключова потреба та головна вимога технологічного суспільства нині екстенсивно поширюється за межі ІКТ-галузі та швидко набуває статусу значущого інструмента, необхідного для ефективної реалізації будь-якої інформаційної діяльності як з використанням ІКТ, так без їх використання. Цей інструментарій створює нові можливості та перспективи для підвищення ефективності будь-якого виду професійної освітньої діяльності у вищій освіті як шляхом розробки алгоритмів для вирішення проблем, що повністю належать до сфери ІКТ, так і алгоритмів без використання ІКТ, які надають чіткі технологічні покрокові інструкції для вирішення різноманітних освітніх проблем. Попри те, що увага до алгоритмічного мислення як наукового феномену зростає, досліджень, спрямованих на визначення змісту алгоритмічного мислення в спостережуваних і вимірюваних характеристиках, ще не проводилось, а його величезний потенціал ще не розкритий. Метою цього дослідження є виявлення, уточнення та категоризація змісту алгоритмічного мислення у спостережуваних і вимірюваних характеристиках: знання, уміння та здібності. Проведене дослідження поєднує кількісні та якісні методи і було реалізовано в 4 етапи: 1) аналіз існуючих наукових джерел з проблеми  алгоритмічного мислення з метою виокремлення сукупності характеристик (знань, умінь та здібностей), які використовуються для його визначення; 2) розробка опитувальника для визначення змісту алгоритмічного мислення, який базується на основі п’ятикрокової універсальної послідовності розробки алгоритму; 3) проведення опитування серед широкого спектра освітян (N = 117); 4) аналіз даних з  метою отримання змісту алгоритмічного мислення у спостережуваних і вимірюваних характеристиках: знання, уміння та здібності. Розроблений опитувальник також базується на розгляді алгоритмічного мислення як складного явища, що інтегрує п’ять типів мислення: абстрактне, логічне, образне, концептуальне та конструктивне. Опитування здійснювалось із залученням 117 експертів-освітян (11 викладачів, які читають курси з алгоритмів та інформатики, 23 практикуючих учителів інформатики, 35 студентів 3-4 курсів підготовки вчителів інформатики та 48 магістрів з інформатики). Експертна  оцінка сукупності спостережуваних і вимірюваних характеристик змісту алгоритмічного мислення відбувалась за допомогою шкали Лайкерта. У результаті отримано сто спостережуваних і вимірюваних показників змісту алгоритмічного мислення (32 показники знань, 38 показників умінь та 30 показників здібностей).